Validation of cyber security behaviour among adolescents at Malaysia university: Revisiting gender as a role - Ting, Tin Tin; Cheah, Kar Man; Khiew, Jie Xin; Lee, Yung Chin; Chaw, Jun Kit; Teoh, Chong Keat (International Journal of Innovative Research and Scientific Studies, 2024)
Cyber-attacks and crimes are still a problem in Malaysia. COVID-19 has pushed Malaysians into the digital world more quickly. These cyberattacks may rise and affect more people. Thus, the aim of this study is to find out if there is a significant difference in the level of cyber security behaviour between males and females in the aspects of malware, password usage, phishing, social engineering and online scamming in Malaysia. An online questionnaire survey was used to gather data from Malaysia and received 207 total responses. Cronbach’s alpha is used to measure questionnaire items’ reliability. A t-test is used to determine the differences between male and female cyber security behaviour. The results show that there is no significant difference between males and females in four aspects out of five, which are malware, password usage, phishing and social engineering. There is a significant difference between males and females in the aspect of online scams. This research helps those who formulate education policies by determining that there is no noticeable gender difference. Men should get the same level of education and training as women. The findings also demonstrate that women’s awareness of technology is increasing.